Statin use and the risk of tubulointerstitial nephritis: a real-world signal detection analysis using FDA Adverse Event Reporting System - Yasmeen, Ayesha; Syed, Mamoon H.; Khardali, Amani; Almansour, Hadi A.; Alshammari, Thamir M. (Frontiers in Medicine, 2025)
BackgroundStatins are widely prescribed for cardiovascular risk reduction but have been linked to a range of adverse effects. Tubulointerstitial nephritis (TIN), a potentially serious renal condition, has been sporadically reported with statin use. This study aims to evaluate the association between statins and TIN using real-world pharmacovigilance data.MethodsWe analyzed adverse event reports from the U.S. FDA Adverse Event Reporting System (FAERS) between 2017 and 2024. Cases of TIN associated with statins were identified using MedDRA Preferred Terms. Disproportionality analyses—including Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Empirical Bayes Geometric Mean (EBGM), and Information Component (IC)—were applied to detect safety signals, stratified by pre- and post-COVID-19 periods.ResultsA total of 120 TIN cases linked to statin use were identified. While no significant signal was detected prior to 2020, consistent signal emergence was noted from 2021 onwards. In 2024, all signal metrics peaked (e.g., ROR 5.77; PRR 5.75; EBGM 5.32; IC 2.41), meeting thresholds for signal detection. Most reports involved patients aged ≥ 60 years and over 65% resulted in hospitalization. Geographic analysis showed wide international distribution, with the majority of reports from the United States and Europe.ConclusionThis real-world analysis identifies a statistically significant disproportionality signal that indicates a possible association between statin use and TIN, particularly in older adults. Clinicians may consider TIN in patients presenting with unexplained renal dysfunction while on statins. Further research is warranted to evaluate this association and identify patient-level risk factors.